Outpatient Clinic of Russian Red Cross in Berlin in 1920s —1930s - K. D. Kotelnikov (Научный диалог)
The documents of the League of Nations archive concerning the history of a unique emigrant institution — the Russian Ambulatory in Berlin are introduced into scientific circulation in the article. It is reported that for at least 17 years (since 1920), the clinic had pro-vided free assistance to the poor. The annual reports and correspondence of the clinic make it possible not only to assess the scale of the activities of the philanthropists of Russian Berlin and their humanitarian significance, but also to analyze information about the social and demographic processes in the emigrant community in the 1920s—1930s. It is noted that from 1920 to 1934 the clinic received 171,955 patients (more than one and a half thousand people a year, of all ages and nationalities). Information is given that doctors treated a wide range of diseases: cardiovascular, nervous, venereal, respiratory and digestive system, urogenital system, eye and ear, the consequences of injuries and trauma. It has been established that the outpatient clinic distributed free medicines, food, and basic necessities since the early 1930s and provided lunches and places in the Salvation Army dormitory for the homeless. The statistics of the clinic are presented with data on the ethnic composition of Russian Berlin (the most representative of the known ones), the aging of emigration in Germany, and the low birth rate in the 1930s and the spread of poverty associated with the Great Depression.